Bilateral extrarenal arteries supplying the kidneys - M. B. Chandan; N. Anandaramajayan; Vasudha Kulkarni (Muller Journal of Medical Sciences and Research, 2025)
Renal vasculature accounts for 20% of cardiac output. The branching pattern of the renal artery supplying the kidney relies on its embryological development. The prevalence of renal vascular abnormalities varies from 25% to 61%. During the routine dissection of a 70-year-old female cadaver at Department of anatomy, Akash institute of Medical Sciences and Research Centre, Bengaluru, we observed bilateral aberrant renal arteries supplying to the superior pole of the right and left kidneys. On further dissection, we observed two accessory renal arteries supplying the hilum of the right kidney and the left kidney. One of the accessory renal arteries bifurcated and then entered the hilum of the left kidney. Knowledge of these renal vascular variations is essential for radiologists, nephrologists, and urologists while performing angiographic studies, aneurysmorphic procedures, or while performing uroradiological procedures.